Transcription pausing: biological significance of thermal fluctuations biased by repetitive genomic sequences. Issue 3 (27th May 2018) - Imashimizu, Masahiko; Lukatsky, David B.
ABSTRACT: Transcription of DNA by RNA polymerase (RNAP) takes place in a cell environment dominated by thermal fluctuations. How are transcription reactions including initiation, elongation, and termination on genomic DNA so well-controlled during such fluctuations? A recent statistical mechanical approach using high-throughput sequencing data reveals that repetitive DNA sequence elements embedded into a genomic sequence provide the key mechanism to functionally bias the fluctuations of transcription elongation complexes. In particular, during elongation pausing, such repetitive sequence elements can increase the magnitude of one-dimensional diffusion of the RNAP enzyme on the DNA upstream of the pausing site, generating a large variation in the dwell times of RNAP pausing under the control of these genomic signals.